2018
DOI: 10.3389/fmicb.2018.01268
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus DNA Enhances Diptericin Expression and Increases Hemocyte Numbers in Drosophila melanogaster via the Immune Deficiency Pathway

Abstract: Infection with the Epstein-Barr virus (EBV) is associated with several malignancies and autoimmune diseases in humans. The following EBV infection and establishment of latency, recurrences frequently occur resulting in potential viral DNA shedding, which may then trigger the activation of immune pathways. We have previously demonstrated that levels of the pro-inflammatory cytokine IL-17, which is associated with several autoimmune diseases, are increased in response to EBV DNA injection in mice. Whether other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…In a previous study, we reported that EBV DNA enhances the production of the proinflammatory cytokine IL-17A as well as IL-23, tumor necrosis factor (TNF-␣), and IFN-␥ when injected into mice (25,65). IL-17A plays a role in host defenses against bacterial and fungal infections (26).…”
mentioning
confidence: 99%
“…In a previous study, we reported that EBV DNA enhances the production of the proinflammatory cytokine IL-17A as well as IL-23, tumor necrosis factor (TNF-␣), and IFN-␥ when injected into mice (25,65). IL-17A plays a role in host defenses against bacterial and fungal infections (26).…”
mentioning
confidence: 99%
“…Our results show that melanized spots (or pseudo-tumors), which have been reported as the hallmarks of a “leukemia-like” phenotype in Drosophila, may not reflect an actual increase in hemocytes. Additionally, studies have used the strong driver Cg-Gal4, which drives expression in fatbody as well as the blood cells 25 , 66 , 67 . As our results show that the ectopic expression of genes in the fatbody may indeed lead to an increase in circulating hemocytes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Shockingly infection induced in flies by vesicular stomatitis virus in toll-7 depleted flies where 50% flies displayed death after 18 days, suggesting HIV infection could also kill toll7 mutant flies, as toll mutant flies displayed fungal invasion, this yet to be confirmed [44]. Alternative to this only viral DNA had been shown in a recent study to evoke immune activation in Drosophila by injecting it in thoracic region [87]. Kaposi sarcoma associated Herpesvirus (KSHV) needs a model which is yet to be studied in flies, however the KSHV viral gene latent nuclear antigen (LANA) interacts with RING3 of human which is homologous to drosophila female sterile homeotic (fsh) has already been identified [127].…”
Section: Future Perspectivementioning
confidence: 98%
“…Expression of BRLF1 and BZLF1 genes using GMR-R model in Drosophila showed BRLF1 caused overproliferation of cells in flies whereas, BZLF1 resulted in interaction with several tumor suppressor genes and both viral genes showed interactions with core tumor suppressor genes like reaper, p53, Rab5, and Tor [86]. EVB DNA injection in flies caused Imd mediated pathway to increase diptericin production at the same time hemocyte proliferation and remarkable increase in numbers of hemocyte cells [87]. Human cytomegalovirus derived immediate early gene transfection in flies resulted in embryonic lethality similar to humans [88].…”
Section: Hiv Modelsmentioning
confidence: 99%